Pay determination in the civil service since 1979 - Kessler, I (1993)
This article traces the development of pay determination in the British civil service over the last decade. It argues that after a period of instability, the pay system established at the end of the 1980s embraced rather than reconciled two competing traditions of pay determination; one based upon the importance of traditional compatibility criteria and the other stressing flexibility to meet managerial needs. As a consequence of the difficulties which emerged under these new arrangements, neither the unions nor the government have fully achieved their pay objectives. While the creation of executive agencies may herald a more fundamental change in pay determination based upon devolved structures and systems, the nature and extent of this change still depends upon resolution of the tension between competing central government concerns to retain financial control and allow agencies to adapt to meet local needs and circumstances.